Lyrics Training: An E-learning Approach to Improve Listening Skills - Martínez, Verónica (2023)
Due to the COVID-19 pandemic, educational agents have been forced to apply strategies and methodologies and use new technological tools that allow them to continue with the teaching–learning processes. Because of this, the present research implements an innovative methodology to analyze the contribution of the Lyrics Training method in the development of listening skills for English language improvement. The experiment was carried out with high school seniors from an academic unit in the city of Ambato. A sample of 62 students was divided into two groups, an experimental group and a control group, each of 31 learners. When comparing both groups through a t-student test for independent samples, the results showed a p-value lower than 0.05 and a Cohen’s d coefficient higher than 0.8, establishing that the teaching process through the Lyrics Training methodology is efficient. Finally, to verify if the Lyrics Training method is suitable for the selected experimental group, the usability scale (SUS) was applied, in which an average acceptance of more than 70 points was obtained, indicating that, in general terms, the Lyrics Training method through a web page is efficient for teaching the English language.